Divergence, convergence, and the history-augmented Solow model - Vadim Kufenko; Klaus Prettner; Vincent Geloso (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
We test the history-augmented Solow model with respect to its predictions on the patterns of divergence and convergence between the nowadays industrialized countries of the OECD. We show that the dispersion of incomes increased after the Industrial Revolution, peaked during the Second World War, and decreased afterwards. This pattern is fully consistent with the transitional dynamics implied by the history-augmented Solow model.
urn:nbn:de:bsz:100-opus-13790
Keywords: J11; O11; O47; 330; history-augmented Solow model; divergence; convergence; cross-country inequality